An update on indirect prosthodontic materials and their manufacturing techniques. (2nd September 2021) - Gray, David; Barraclough, Olivia; Ali, Zaid; Nattress, Brian
Abstract : Innovations in the fabrication of removable partial dentures depend not only on the development of new materials, but also on the availability of manufacturing techniques that can be applied to a dental environment. Many of these new materials have limited clinical evaluations, hence it can be difficult for the general dental practitioner to confidently determine which materials to use. The introduction of any new material into clinical practice often requires practitioners to go through a learning curve to make the most of the material and employ it most appropriately. This article provides an update on the materials available for removable partial dentures and discusses the advantages and disadvantages to enable the GDP to make an evidence-based decision. CPD/Clinical Relevance: It is important that clinicians are aware of the alternative materials to conventional acrylic and cobalt chrome.